Actinomycosis of the orbit. - Sullivan, T J (1992)
Actinomycosis is a very rare cause of orbital abscess usually attributable to direct spread from adjacent structures. A case of actinomycosis of the orbit is presented, which was treated as orbital pseudotumour for 3 months before progression of signs and symptoms, despite high dose steroids, led to the diagnosis being reconsidered.